An Analysis of Patient-Reported Recovery Outcomes of Topical Tripeptide/Hexapeptide Formulations Utilized in a Prospective Randomized Double-Blind Split Neck and Body Study. Issue 1 (18th November 2020) - Casas, Laurie A; Bell, Michaela; Claytor, Brannon; Ziegler, Mary E; Widgerow, Alan D
Abstract: Background: Physicians strive to improve the postsurgical experience and optimize patient-reported recovery outcome measures (PROMs) following elective cosmetic surgical procedures. Our previous pilot feasibility study demonstrated that twice daily postoperative topical body treatment with tripeptide and hexapeptide (TransFORM Body Treatment with TriHex Technology [TFB, Alastin Skincare, Inc., Carlsbad, CA]) reduced PROMs of swelling, induration, soft tissue fibrosis, and pain as well as improved visible and palpable skin quality. Objectives: Evaluate whether adding a tripeptide/hexapeptide anhydrous gel (Regenerating Skin Nectar with TriHex Technology [RSN, Alastin Skincare, Inc., Carlsbad, CA]) pre- and post-procedure to the existing postsurgical regimen of TFB significantly improves 6 PROMs in patients undergoing neck and body contouring cosmetic surgical procedures. Methods: Ten female patients underwent 15 neck and body contouring procedures and were blindly randomized to 1 of 2 topical treatment protocols (1 [TFB] and 2 [RSN/TFB]) pre- and post-procedure. Patient-reported scores of 5 skin parameters (skin discoloration, ecchymosis, edema, induration, and subcutaneous fibrous banding) and pain scores using the Visual Analog Scale were collected at 8 intervals for 12 weeks post-procedure. Results: The treatment side that used both topicals showed significantly reduced scores of edema, induration, and subcutaneous fibrous banding compared with the side that only used 1 topical, on days 5–7 and 10–14 ( P < 0.05). All patients observed slower soft tissue recovery on the side that was treated with TFB alone and opted to break the code and use both topical treatments. Conclusions: Patients had statistically significant improved patient-reported measures of skin edema, skin induration, and subcutaneous banding on the operated side that used both topicals. Level of Evidence: 2: